1970
DOI: 10.1017/s0022172400028461
|View full text |Cite
|
Sign up to set email alerts
|

The role of normal skin in the spread of streptococcal pyoderma

Abstract: SUMMARYThe primary body site of acquisition of group A streptococci was examined prospectively in a population with endemic streptococcal pyoderma. Weekly cultures were obtained during the skin infection season from apparently normal upper respiratory and cutaneous sites (and from skin lesions when present) in 44 children and adults living on the Red Lake Indian Reservation.During the 9-week period of the study 705 of a total of 2305 cultures were positive for group A streptococci. The percentage of positive c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

1972
1972
1998
1998

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(20 citation statements)
references
References 14 publications
1
19
0
Order By: Relevance
“…In family 1 (see Fig. 4 Studies carried out at the Red Lake Indian Reservation in 1968 revealed that a primary factor in the development of pyoderma was previous acquisition of streptococci on the normal skin (10). The present study confirms these findings with observations at more frequent intervals and extends them to include several other pyoderma strains, including a serotype (M-57) with nephritogenic properties.…”
Section: Methodssupporting
confidence: 84%
See 2 more Smart Citations
“…In family 1 (see Fig. 4 Studies carried out at the Red Lake Indian Reservation in 1968 revealed that a primary factor in the development of pyoderma was previous acquisition of streptococci on the normal skin (10). The present study confirms these findings with observations at more frequent intervals and extends them to include several other pyoderma strains, including a serotype (M-57) with nephritogenic properties.…”
Section: Methodssupporting
confidence: 84%
“…8): 55). This report and the earlier ones from this laboratory (5,10,23) were based on observations at less frequent intervals.…”
Section: Methodsmentioning
confidence: 85%
See 1 more Smart Citation
“…While the Red Lake outbreak in the northern USA showed that cold climates were not inimical to the disease, our and other studies suggested that hot and sweaty skin in physically tired men was particularly susceptible. There is general agreement that streptococci do not penetrate normal intact skin and that a breach of the epidermis by trauma, insect bite or invasion by scabies, mites or other parasites must precede the infection (Dudding et al 1970).…”
Section: Discussionmentioning
confidence: 99%
“…Environmental samples were taken with cotton swabs dipped in Todd -Hewitt broth (12). On the pillowcase and floor, an area of 5 cm in diameter was rubbed with the swab.…”
Section: Bacteriologymentioning
confidence: 99%